ANALISIS RENCANA TATA RUANG WILAYAH (RTRW) KOTA SABANG BERDASARKAN PETA JALUR PATAHAN AKTIF DI KOTA SABANG - Sjafrizal .; Faisal Abdullah; Nazli Ismail; Laura Vadzla Hermansyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
There are two major faults in Pulau Weh (Weh Island): Sabang fault and Seuke fault. This research is conducted in Pulau Weh, Sabang, Province of Aceh to map the distribution of major and minor fault lines in that area and analyze the conformity of the development plan to the existing active fault lines based on Spatial Planning and Territory. The fault lines mapping process based on secondary data published by Directorate of Mineral Resource Inventory, Geothermal sub-directorate and fault line. The fault lines distribution then compared with the data from government policy document and the Spatial Planning and Territory of Sabang that issued by Sabang government, which provided detailed information about the development process and the long-term development plan of Sabang. The analysis more focused on how development distribution and development planning of Sabang based on disaster mitigation in the future. The result shows that most of spatial pattern and structure set in Spatial Planning and Territory by the Sabang City government are located on active fault which can become disaster-prone areas. The process of development planning in Sabang so far has not studied the potential of development conformity and the distribution of active faults in Sabang. Ie Meulee, Ujong Kareung, and Anoe Itam are the area that can use as the alternative area because they not traversed by the major and the minor faults.